Cardiovascular risk profiling among South Asian adults in Hong Kong: a latent class analysis - Gary Ka-Ki Chung; Woohyung Lee; Danna Camille Vargas; Bulbul Sharma; Kai Sing Sun; Heidi Hung; Lee Sha Tong; Tsz Lui Tang; Hasiba Munir; Chi Yui Wong; Soniya Pun; Man Hin Chio; et al. (International Journal for Equity in Health)
Abstract Background South Asians living in urbanized settings are facing disproportionate cardiovascular burden largely attributable to modifiable risk factors. Given the rapid surge in South Asian population in Hong Kong, this study aims to identify and distinguish clusters of cardiovascular risk profiles among community-dwelling South Asian adults. Methods Between June 2022 and December 2023, 1181 South Asian adults were recruited through territory-wide outreach health assessments on lifestyle, psychological distress, obesity, clinical cardiovascular conditions, and sociodemographic factors. Latent class analysis was performed to classify the cardiovascular profiles, followed by multinomial logistic regression to identify the sociodemographic characteristics across classes. Results Five latent classes were identified: low risk (19.6%), lifestyle risk plus distress (8.9%), obesity risk (33.4%), lifestyle risk plus distress with obesity (26.6%), and high clinical risk (11.4%). Apart from the higher clinical risk in older adults, women tended to cluster into classes with obesity, while men and the economically active were more likely in classes with poorer lifestyles and stress. Pakistani and Nepalese consistently exhibited higher risks compared to Indians, whereas the less educated tended to cluster into the high clinical risk class. Conclusion This study revealed distinct cardiovascular risk patterns and sociodemographic features within the South Asian community in Hong Kong. The heavy burden on obesity especially in women, lifestyle and psychological risks especially in men, and low overall physical activity level may be translated into a tremendous cardiovascular disease burden in the forthcoming decades, in particular among Pakistani and Nepalese as well as the socioeconomically disadvantaged.